PERSEPSI PENGUNJUNG TERHADAP KUALITAS PELAYANAN DI OBJEK WISATA TAMAN REKREASI ALAM MAYANG KOTA PEKANBARU - Ananda, Ingrid Dwi; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The research purposed to get known about the visitor's perception of the quality of service in attractions tourism of recreation park Alam Mayang Pekanbaru. This research is quantitative descriptive research with respondents consisted of 50 people visitors came to the Recreation Park Mayang Pekanbaru, selection of the study sample using technique accidental sampling. Data collection was done by observation, questionnaires/question form, and documentation. Based on the research that has been done, it show that the characteristics of visitors are mostly women, 60% and 40%, mostly a student and come from local visitors. The visitor's perception of the quality of service is obtained based on the tangibles (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and empathy (empathy) is already good enough and visitors already feel quite satisfied with the service. Keywords: Visitor Perception, Service Quality